Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/cne.24620
|View full text |Cite
|
Sign up to set email alerts
|

The brain of the tree pangolin (Manis tricuspis). IV. The hippocampal formation

Abstract: Employing a range of standard and immunohistochemical stains we provide a description of the hippocampal formation in the brain of the tree pangolin. For the most part, the architecture, chemical neuroanatomy, and topological relationships of the component parts of the hippocampal formation of the tree pangolin were consistent with that observed in other mammalian species. Within the hippocampus proper fields CA1, 3, and 4 could be identified with certainty, while CA2 was tentatively identified as a small tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 69 publications
3
16
0
Order By: Relevance
“…Here, we continue our systematic analysis of the brain of the tree pangolin (Imam, Ajao, Bhagwandin, Ihunwo, & Manger, ; Imam, Bhagwandin, Ajao, Spocter, et al, ; Imam, Bhagwandin, Ajao, Ihunwo, Fuxe, et al, ; Imam, Bhagwandin, Ajao, Ihunwo, & Manger, ) by providing a detailed account of the architecture of the tree pangolin diencephalon and hypothalamus using Nissl and myelin staining in conjunction with a range of immunohistochemical stains.…”
Section: Introductionmentioning
confidence: 83%
“…Here, we continue our systematic analysis of the brain of the tree pangolin (Imam, Ajao, Bhagwandin, Ihunwo, & Manger, ; Imam, Bhagwandin, Ajao, Spocter, et al, ; Imam, Bhagwandin, Ajao, Ihunwo, Fuxe, et al, ; Imam, Bhagwandin, Ajao, Ihunwo, & Manger, ) by providing a detailed account of the architecture of the tree pangolin diencephalon and hypothalamus using Nissl and myelin staining in conjunction with a range of immunohistochemical stains.…”
Section: Introductionmentioning
confidence: 83%
“…Our analysis revealed no clear indications of the presence of either the CA2 or CA4 fields in both species of carnivore studied. Previous investigations of the cornu Ammonis region in other carnivores, such as the domestic dog, and closely related species, such as the tree pangolin, have hinted at the possible presence of the CA2 field (Amayasu et al, 1999; Hof et al, 1996; Imam et al, 2019), but this field is reported to be absent in the domestic cat (Hirama et al, 1997), and was not noted in the red fox (Amrein & Slomianka, 2010). Despite this, the CA2 region is regularly reported as a distinct field in the laboratory rat/mouse and primates, and has been associated specifically with social memory (e.g., Botcher et al, 2014; Dudek, Alexander, & Farris, 2016; Hitti & Siegelbaum, 2014; Kohara et al, 2014; Tzakis & Holahan, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, immunostaining for vesicular glutamate transporter 2 clearly revealed two of these sublamina of the molecular layer of the dentate gyrus in the banded mongoose, but this immunostain did not reveal these sublamina in the domestic ferret. In the African elephant, up to four sublaminae of the molecular layer were revealed with calretinin immunostaining (Patzke et al, 2014), while in the tree pangolin vesicular glutamate transporter 2, calbindin and calretinin immunostaining revealed the presence of three sublaminae (Imam et al, 2019), matching that observed in laboratory rodents (Witter, 2007). In most mammals the granule cell layer is considered a single entity with no sublamina (Witter, 2007), but in the present study vesicular glutamate transporter 2 immunostaining revealed the presence of three sublaminae in the banded mongoose (outer, middle, and inner) but not the domestic ferret.…”
Section: The Sublamination Of the Dentate Gyrusmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we expand our systematic analysis of the brain of the tree pangolin (Imam, Ajao, Bhagwandin, Ihunwo, & Manger, ; Imam et al, ; Imam et al, ; Imam, Bhagwandin, Ajao, Ihunwo, & Manger, ; Imam, Bhagwandin, Ajao, & Manger, ) by providing a detailed account of the architecture of the tree pangolin brainstem and cerebellum (diencephalic prosomere 1 through to rhombomere 11) using Nissl and myelin staining in conjunction with a range of immunohistochemical stains.…”
Section: Introductionmentioning
confidence: 99%